Gobies (Teleostei: Gobiidae) of the oldest and deepest Caspian Sea sub-basin: an evidence-based annotated checklist and a key for species identification - Zarei, Fatah; Esmaeili, Hamid Reza; Abbasi, Keyvan; Kovačić, Marcelo; Schliewen, Ulrich K.; Stepien, Carol A. (Zootaxa, 2022)
An evidence-based annotated checklist of gobiid species (Teleostei: Gobiidae) inhabiting the South Caspian Sea and its catchment area (i.e., the South Caspian Sea sub-basin) is compiled. The South Caspian Sea sub-basin gobiofauna currently comprises 38 confirmed species in 11 genera (i.e., 88.4% of the Caspian gobiofauna); the most diverse genus is Benthophilus (16 species, 42.1%), followed by Ponticola (seven species, 18.4%), and Neogobius (four species, 10.5%). Ten species (26.3%) are endemic to the South Caspian Sea sub-basin, another 21 species (55.3%) are endemic in the Caspian Sea basin as a whole, six (15.8%) are native to the Ponto-Caspian region, and one species (2.6%) is exotic. According to the current IUCN Red List, 24 species (64.9%) are listed as being of “Least Concern”, eight species (21.6%) are “Data Deficient”, and five species (13.5%) as “Not Evaluated”. Similar numbers of species are confirmed to inhabit the South Caspian Sea sub-basin waters of the three countries that border it: Iran harbors 25 species (nine genera), Azerbaijan has 28 species (10 genera), and Turkmenistan has 26 species (10 genera). The greatest known diversity of Benthophilus in South Caspian waters occurs in Azerbaijan and Turkmenistan (11 species each), whereas Iranian waters harbor seven species. In comparison, Iran, with six out of eight species (75%), has the greatest diversity of Ponticola known from the Caspian Sea basin. Species richness and endemism of the Caspian Sea gobiid-fauna varies considerably with latitude: the North, Middle and South sub-basins respectively harbor 21, 31, and 37 native species, of which 0, 3, and 10 species are endemic in that sub-basin alone. The high species diversity and endemism of Gobiidae in the South Caspian Sea sub-basin may have resulted from: (i) greater ecological diversity compared to the northern Caspian Sea marine areas (e.g., water depths) that may have led to differential niche adaptation and adaptive radiation in the Benthophilus-Anatirostrum species flock, (ii) lower historical extinction rate compared to Caspian higher latitudes, which had greater exposure to the Pleistocene’s extreme climatic changes, (iii) geological history of freshwater habitats in the South Caspian Sea sub-basin that set the speciation and evolutionary stage for the genus Ponticola during these Pleistocene climatic oscillations, (iv) presently less limiting conditions compared to the North Caspian Sea, i.e., higher present winter minimum of water temperature and higher salinity, and (v) Iranian freshwater abundance, variability and habitat diversity. Contemporary gobiid diversity and endemism in the Caspian Sea basin suggests two higher-priority conservation areas: (i) freshwater habitats of the South Caspian Sea region in Iran and Azerbaijan, and (ii) shallow coastal and deep waters of the South and Middle Caspian Sea sub-basins. An identification key is provided for the updated gobiid species from the South Caspian Sea sub-basin.